First FHM3 mouse model shows spontaneous cortical spreading depolarizations. Issue 1 (27th December 2019) - Jansen, Nico A.; Dehghani, Anisa; Linssen, Margot M. L.; Breukel, Cor; Tolner, Else A.; van den Maagdenberg, Arn M. J. M.
Abstract: Here we show, for the first time, spontaneous cortical spreading depolarization (CSD) events – the electrophysiological correlate of the migraine aura – in animals by using the first generated familial hemiplegic migraine type 3 (FHM3) transgenic mouse model. The mutant mice express L263V‐mutated α 1 subunits in voltage‐gated NaV 1.1 sodium channels ( Scn1a L263V ). CSDs consistently propagated from visual to motor cortex, recapitulating what has been shown in patients with migraine with aura. This model may be valuable for the preclinical study of migraine with aura and other diseases in which spreading depolarization is a prominent feature.